SOCIAL MEDIA: IMPACT ON BUSINESS ACTIVITY - Chyrak, Iryna; Virkovska, Anastasiya; Koziuk, Viktor; Kiziloglu, Mehmet (Socio-economic relations in the digital society, 2023)
Social media is extremely popular among users all over the world. Social media is becoming not only a means of communication, but also a powerful platform for conducting business. The purpose of the research is to analyze the use of modern social media tools and determine their impact on the purchasing behaviour of Internet users and the effectiveness of online business. The paper analyzes the features and trends in social media use, as well as the reasons for their growing popularity among users around the world. An analysis of the social media influence on business development was carried out and several significant advantages were identified, in particular: expansion of information sources about the company’s activities, coverage of a larger target audience, reduction of company costs, implementation of advertising and promotion of product sales, etc. The effective use of modern social media tools and the latest methods of economic and psychological influence on the purchasing behaviour of users has been analyzed. It was determined that there is a close relationship between the effectiveness of business development in social media and the use of social media marketing (SMM) tools, Internet advertising, customer relationship management (CRM), SEO optimization of websites, mobile applications, the use of virtual reality, etc. Based on the research, a strategy for conducting business in social media is proposed, which involves: 1) determining the target audience for effective positioning of products and the correct choice of the social network; 2) definition and coordination of the company’s long-term goals in its offline and online activities; 3) generation of high-quality unique content and constant work on its filling; 4) selection of social media tools to increase the effectiveness of attracting potential customers, sales promotion and automation of business processes; 5) conducting media analytics, i.e. monitoring the effectiveness of business activities in social media.